Relationship between Reinforcement Diameter and Bond Stress in High Performance Lightweight Concrete - Tugrul, Esra; Alyamaç, Kürşat Esat; Ince, Ragip; Ulucan, Zülfü Çınar (My University, 2021)
High performance lightweight concrete (HPLC) is a new and original research in structural engineering. Due to the high risk of earthquakes, which is one of the biggest disasters today, the need for HPLCs has increased. The purpose of this study is to experimentally research concrete-reinforcement bond for the change parameters such as different reinforcement diameters and different embedded lengths. For this purpose, HPLCs with different mix ratios and different concrete components were prepared by using pumice aggregates. Within this scope, HPLC beam specimens of 100×180×800 mm dimensions were prepared and produced specimens were subjected to the Standard Belgium Hinged Beam (SBHB) test. There are limited studies in the literature on the investigation of the bond properties of HPLC beams with this test. The mentioned study draws attention with this aspect. In the present study, ribbed steel reinforcement bars with different diameters were used. The beam specimens were produced considering the different embedded lengths for each reinforcement diameter. The bond tests were performed. Using the load applied vertically and read with the help of the load cell in the experiment, the bond stress occurring in the reinforcement was calculated with the help of the force in the reinforcement indirectly found. As a result of the experiments, it has been determined that there is a significant relationship between bond stress and reinforcement diameter and embedded length. It has been determined that the bond stress decreases with the increase of reinforcement diameter and embedded length.
Keywords: Beam; High Performance Lightweight Concrete (HPLC); Bond stress; Reinforcement diameter; Embedded length